Strengthening Anticorruption Character at Elementary Schools in Indonesia: Study on Instructional Practices by In-Service Islamic Education Teachers - Abdul Kholiq (UIN Siber Syekh Nurjati Cirebon, 2022)
AbstractThe corruption phenomenon in Indonesia must get all partiesâ€™ attention, including education. The failure to resolve it seriously will lead to the nationâ€™s destruction. This study aimed to explore how anti-corruption characters were integrated into Islamic education instruction at elementary schools. This study used a qualitative descriptive method focusing on Islamic education instructional practices of 10 in-service teachers involved in the Professional Teacher Education Program Universitas Islam Negeri Walisongo Semarang. Data were collected through documentation and observation and were analyzed using descriptive analytical techniques. The results of this study proved that Islamic education subjects could be a good medium for strengthening anti-corruption characters through integrating anti-corruption values in Islamic education instruction. Hence, to become a massive movement, it is necessary to formulate more operational and binding policies to conduct anti-corruption education at all levels of education, especially at elementary school levels.Keywords: anti-corruption characters, Islamic education, integration, professional teacher education program, instruction.Â AbstrakFenomena korupsi di Indonesia harus mendapatkan perhatian dari semua pihak, termasuk dunia pendidikan. Kalau tidak diselesaikan secara serius, korupsi di Indonesia dapat membawa negara Indonesia menuju kehancuran. Penelitian ini bertujuan untuk mengetahui bagaimana karakter antikorupsi diintegrasikan dalam pembelajaran Pendidikan Agama Islam (PAI) Sekolah Dasar. Penelitian ini menggunakan metode kualitatif deskriptif yang berfokus pada praktek pembelajaran PAI 10 guru yang terlibat dalam Pendidikan Profesi Guru (PPG) Dalam Jabatan Universitas Islam Negeri Walisongo Semarang. Data dikumpulkan melalui dokumentasi dan observasi, dan selanjutnya dianalisis dengan teknik deskriptif analitis. Hasil penelitian ini membuktikan bahwa mata pelajaran PAI dapat menjadi media yang baik bagi penguatan karakter antikorupsi melalui integrasi nilai-nilai antikorupsi dalam pembelajaran PAI. Sehingga, agar menjadi gerakan yang massif perlu dirumuskan kebijakan yang lebih operasional dan mengikat untuk menyelenggaran pendidikan antikorupsi pada semua jenjang Pendidikan, khususnya pada jenjang sekolah dasar.Kata kunci: karakter antikorupsi, Pendidikan Agama Islam, integrasi, Pendidikan Profesi Guru, pembelajaran.